UPLC-Orbitrap-MS/MS Combined With Biochemical Analysis to Determine the Growth and Development of Mothers and Fetuses in Different Gestation Periods on Tibetan Sow Model - Zhang, Longmiao; Tan, Chengquan; Xin, Zhongquan; Huang, Shuangbo; Ma, Junwu; Zhang, Meiyu; Shu, Gang; Luo, Hefeng; Deng, Baichuan; Jiang, Qingyan; Deng, Jinping (Frontiers in Nutrition, 2022)
Pregnancy is a complex and dynamic process, the physiological and metabolite changes of the mother are affected by different pregnancy stages, but little information is available about their changes and potential mechanisms during pregnancy, especially in blood and amniotic fluid. Here, the maternal metabolism rules at different pregnancy stages were investigated by using a Tibetan sow model to analyze the physiological hormones and nutrient metabolism characteristics of maternal serum and amniotic fluid as well as their correlations with each other. Our results showed that amniotic fluid had a decrease (P < 0.05) in the concentrations of glucose, insulin and hepatocyte growth factor as pregnancy progressed, while maternal serum exhibited the highest concentrations of glucose and insulin at 75 days of gestation (P < 0.05), and a significant positive correlation (P < 0.05) between insulin and citric acid. Additionally, T4 and cortisol had the highest levels during late gestation (P < 0.05). Furthermore, metabolomics analysis revealed significant enrichment in the citrate cycle pathway and the phenylalanine/tyrosine/tryptophan biosynthesis pathway (P < 0.05) with the progress of gestation. This study clarified the adaptive changes of glucose, insulin and citric acid in Tibetan sows during pregnancy as well as the influence of aromatic amino acids, hepatocyte growth factor, cortisol and other physiological indicators on fetal growth and development, providing new clues for the normal development of the mother and the fetus, which may become a promising target for improving the well-being of pregnancy.